Epidermoid Cyst of Sole - Wuriandaru Kurniasih; Arif Widiatmoko (Fakultas Kedokteran Universitas Brawijaya, 2022)
An epidermoid cyst is benign cystic tumor coated with squamous epithelium and contains keratin. It generally appear on the body parts which have pilosebaceous follicles, such as head, neck, and body. The manifestation of the disease is a skin-colored, mobile, painless nodule with a punctum in the center. Epidermoid cyst of sole is often similar to clavus, callus, and verruca plantaris. However, epidermoid cyst of sole is rare because the area is without pilosebaceous follicles. The etiopathology is believed due to trauma that causes implantation of epidermal cells into the dermis layer, thus triggering the formation of epidermoid cysts. This case report a girl with an epidermoid cyst of sole that was initially thought as a verruca plantaris and clavus. A 14-year-old girl complained about a bump on her right foot that got bigger during nine months. The lesions surface was slippery, and the patient felt pain when walking. The patient denied any trauma or changing footwear with friends or relatives. Examination in the right lateral plantar pedis region, a nodule was found skin-colored, round, measuring 2x2 cm, and solitary. The patient was planned to undergo excochleation, but since a white cystic mass was found during the operation, it was continued with extirpation surgery. The histopathological examination results showed a stroma with keratin, which was concluded as an epidermoid cyst. In the case of epidermoid cysts with atypical clinical symptoms and unusual lesion locations, histopathological examination is required for a definite diagnosis.